Experimental and Modeling Investigation of CO3=/OH– Equilibrium Effects on Molten Carbonate Fuel Cell Performance in Carbon Capture Applications - Barckholtz, Timothy A.; Elsen, Heather; Kalamaras, Patricia H.; Kiss, Gabor; Rosen, Jon; Bove, Dario; Audasso, Emilio; Bosio, Barbara (Frontiers in Energy Research, 2021)
Molten Carbonate Fuel Cells (MCFCs) are used today commercially for power production. More recently they have also been considered for carbon capture from industrial and power generation CO2 sources. In this newer application context, our recent studies have shown that at low CO2/H2O cathode gas ratios, water supplements CO2 in the electrochemical process to generate power but not capture CO2. We now report the direct Raman observation of the underlying carbonate-hydroxide equilibrium in an alkali carbonate eutectic near MCFC operating conditions. Our improved electrochemical model built on the experimental equilibrium data adjusts the internal resistance terms and has improved the representation of the MCFC performance. This fundamentally improved model now also includes the temperature dependence of cell performance. It has been validated on experimental data collected in single cell tests. The average error in the simulated voltage is less than 4% even when extreme operating conditions of low CO2 concentration and high current density data are included. With the improvements, this electrochemical model is suitable for simulating industrial cells and stacks employed in a wide variety of carbon capture applications.